Asymptotic behavior of inexact orbits of nonexpansive mappings - Reich, Simeon; Zaslavski, Alexander J. (Topological Methods in Nonlinear Analysis, 2020)
We study the convergence of inexact iterates of nonexpansive mappings which take a nonempty closed subset of a complete metric space into the space in the case where the errors are sufficiently small.